(untitled) (Prithvi Academic Journal, 2019)
There is a growing interest among policymakers and academics around the world about the role of entrepreneurship in the socio-economic development of a country. It is believed that if any society works towards encouraging its people to pursue their careers in creating enterprises through creative ideas it will be able not only to grow economically but will also be able to sustain in the long run. Various factors contribute to the development of entrepreneurship in a society; socio-cultural influence is one of the important factors. Though there are various components of socio-cultural factors, this study focused on the impact of education and training on entrepreneurship development. The method adopted was a cross-sectional survey and the design is descriptive. The findings show that education and training play some roles in making an individual motivated towards entrepreneurship. However, the significance of the influence could not be found in the present study. Therefore, it can be concluded that to develop entrepreneurship in a society, education and training on various dimensions of it should be encouraged by societies for their socio-economic growth.